Genome Mapping by Fluorescent Fingerprinting - Gregory, Simon G.; Howell, Gareth R.; Bentley, David R. (Genome Research, 1997)
The construction of sequence-ready maps of overlapping genomic clones is central to large-scale genome sequencing. We have implemented a method for fluorescent fingerprinting of bacterial clones to assemble contig maps. The method utilizes three spectrally distinct fluorescently tagged dideoxy ATPs to specifically label theHindIII termini in HindIII and Sau3AI restriction digests of clones that are multiplexed prior to electrophoresis and data collection. There is excellent reproducibility of raw data, improved resolution of large fragments, and concordance between the results obtained using this and the equivalent radioactive protocol. This method also allows detection of smaller overlaps between clones when compared to the analysis of restriction digests on nondenaturing agarose gels.